Distinct Cortical Signatures Associated with Sedation and Respiratory Rate Depression by Morphine in a Pediatric Population. (November 2016) - Montandon, Gaspard; Cushing, Sharon L.; Campbell, Fiona; Propst, Evan J.; Horner, Richard L.; Narang, Indra
Abstract : Background: Opioid analgesia is an essential component of perioperative care, but effective analgesia can be limited by excessive sedation and respiratory depression. The cortical signatures associated with sedation by opioids and the relationship between changes in cortical activity and respiratory function are not well understood. The objectives of this study were to identify the electroencephalogram signatures of sedation and respiratory changes induced by morphine in a pediatric population after elective surgery. Methods: After otologic surgery, patients (14.8 ± 2.8 yr, n = 10) stayed overnight for pain relief with morphine (3 to 10 mg), hydration, and clinical observation. Electroencephalogram activity and polysomnography were performed before and after morphine, and electroencephalogram spectral properties and cardiorespiratory activities were analyzed. Results: Compared to wakefulness and non–rapid eye movement sleep, morphine reduced high-frequency β1 (13.5 to 20 Hz) and β2 (20 to 30Hz) electroencephalogram powers (n = 10) and decreased coherence between frontal and occipital β2 electroencephalogram activities (n = 9), therefore indicating that morphine induced a deep sedative state. Morphine also reduced respiratory rate by 8.3% (n = 10). Interestingly, there was a significant correlation between the reduction in β1 electroencephalogram activity and the depression in respiratory rate induced by morphine (R = 0.715, n = 10). With significant reduction in β1 power, respiratory rate was decreased by more than 25%, suggesting that reduction in cortical arousal is associated with the severity of respiratory rate depression. Conclusions: Analgesic doses of morphine are associated with reduction in respiratory rate when accompanied by reduction in β1 electroencephalogram power, indicating a powerful effect of cortical arousal state per se in respiratory rate depression by morphine. Abstract : Morphine reduced frontal high-frequency (β) electroencephalography power and reduced frontal-occipital β coherence. Analgesic doses of morphine are associated with reduction in respiratory rate when accompanied by reduction in β power. These results indicate an effect of cortical arousal state per se in respiratory rate depression by morphine.Supplemental Digital Content is available in the text.